A State‐of‐the‐Art Update on Integrated CO2 Capture and Electrochemical Conversion Systems. Issue 5 (1st February 2022) - Gutiérrez‐Sánchez, Oriol; Bohlen, Barbara; Daems, Nick; Bulut, Metin; Pant, Deepak; Breugelmans, Tom
Abstract: To valorize waste CO2, capturing and utilizing it to produce chemical building blocks is currently receiving a lot of attention. In this respect, amine and alkali base solutions have shown to be efficient CO2 capturing solutions and electrochemical CO2 conversion is a promising technology to convert CO2 and, as such, reduce greenhouse gas emissions. However, to date, CO2 capture and utilization (CCU) technologies have been investigated almost exclusively as separate processes. This has the disadvantage that CO2 has to be desorbed and compressed from the capture solution before sending it to the CO2 electrolyzer, seriously increasing the capital and operational costs of the overall technology. To improve the valorization potential of the CCU technologies, integrating both technologies by directly utilizing the capture solution as an electrolyte for the electrochemical CO2 reduction (eCO2 R) is a highly promising approach. This technology is however limited by low Faradaic efficiencies (FE) and partial current densities that can be achieved with these solutions. The main reason for this is the slow CO2 release rate at the catalytic interphase. Nevertheless, in recent years, in light of tackling these challenges, several studies successfully managed to decrease the costs of the CO2 capturing step and to electrochemically convert more efficiently the CO2 capture solutions. Herein, we review the status of the integrated CO2 capture and electrochemical conversion technology, discussing the recent developments and advances both in the field of CO2 capture and eCO2 R. Abstract : What to do with CO2 : To improve the valorization potential of the Carbon Capture & Utilization technologies, integrating both capture and conversion strategies by directly utilizing the capture solution as an electrolyte for the electrochemical CO2 reduction (eCO2 R) is a highly promising approach. We review the status of the integrated CO2 capture and electrochemical conversion technology, discussing the recent developments and advances both in the field of CO2 capture and eCO2 R.